Analisis Penggunaan SAK EMKM pada Toko Hani Mart Kelurahan Mabar, Kecamatan Medan Deli - Aprida Damayanti Br Sitanggang; Mangasa Sinurat; Dame Ria R Saragih (Jurnal Ekonomi Bisnis dan Akuntansi, 2026)
This study aims to identify and analyze the implementation of the Financial Accounting Standards for Micro, Small, and Medium Entities (SAK EMKM) in the recording and preparation of financial statements at Toko Hani Mart, Mabar Village, Medan Deli District. This study employs a descriptive qualitative method with a case study approach. Data were obtained through interviews with the business owner and documentation of financial transactions covering fixed assets, liabilities, revenues, and expenses. The results show that Toko Hani Mart has not fully implemented SAK EMKM in preparing its financial statements, although daily sales transactions have been recorded using a point-of-sale application. The recognition and measurement of revenue and inventory are consistent with SAK EMKM, whereas the recognition and measurement of fixed assets remain inconsistent due to the absence of acquisition cost records and depreciation calculations. Toko Hani Mart has no liabilities, so its business activities are entirely financed by its own capital, satisfying the criteria for applying SAK EMKM as it has no public accountability. The identified inconsistencies stem from the owner’s limited understanding of SAK EMKM and the absence of training or socialization regarding the standard. This study recommends the preparation of complete financial statements in accordance with SAK EMKM to support more accountable financial management.